Evaluating the Validity of Ahara and Vihara in Ayurveda: Non-Adherence to their Principles as Risk Factors for Disease - Datey, Purnima; Hankey, Alex (An Overview of Disease and Health Research Vol. 2, 2025)
The chronic disease crisis has afflicted humanity for many years. As an insight, diseases related to metabolic syndrome such as cardiovascular disease (CVD) and type 2 diabetes (T2DM) are proving particularly costly, with costs predicted to spiral out of control, particularly in countries in South and East Asia. In Ayurveda, such disease crisis are explained in terms of imbalances in patients’ physiological regulatory systems. Life-style habits—such as smoking, alcohol intake, no exercise etc.—are well-known risk factors for disease, often understood as effects of particular molecules. Patients’ life-styles tend to create ongoing strain on physiological regulation, so that restoring patients’ regulatory systems to states of natural homeostatic and allostatic balance is necessary to restore health. Systems of traditional medicine advise on habits like Yoga practice, timings of meals, retiring to bed and rising. This study present a non-rigorous demonstration of how such influences can be subject to usual contingency table risk-factor analysis. Data were collected from patients at Rasähära Kendra clinics in the city of Bhopal, who completed questionnaires on life-style and health-related habits, health history and current status. Supplementary data was obtained from independently interviewed citizens of Bhopal. Classic risk factor analysis was carried out by using categorical Yes/No variables answering the two questions. The data were analyzed using Excel and pad. The result indicated that a variety of diet and lifestyle factors considered important in South Asian Traditional, Complementary, and Alternative Medicine (TCAM) systems of medicine like Ayurveda and Yoga may be shown to influence values of BMI considered important in metabolic syndrome, and various aspects of Hashimoto’s thyroiditis. Although non-rigorous, results demonstrate how such methods may validate life-style factors from traditional medicine: not observing them increases disease susceptibility. The study concluded that it is practical to obtain and analyse data testing influences of lifestyle factors on the aetiology of various diseases and their complications, as suggested by Ayurveda, and indeed other TCAM systems. Further, more rigorous research should be implemented to validate these findings.